Efeito do treinamento físico sobre a modulação autonômica e tolerância ao exercício de pacientes submetidos à terapia de substituição renal: um estudo caso-controle - SILVA FILHO, Antonio Carlos Pereira (2019)
Aim: We aimed to analyze the effect of an exercise training program in autonomic modulation, exercise tolerance, anxiety, depression and sleep quality of hemodialysis and kidneytransplanted patients. Design: Case-control study Setting: In-hospital Center for Kidney Disease Prevention, São Luís, Brazil Participants: Four groups of patients undergoing hemodialysis and kidney-transplanted subjects had their biochemical tests, and heart rate variability evaluations analyzed. Also, sleep quality, anxiety and depression questionnaires were evaluated. Interventions: Combined exercise training Main outcome measures: Heart rate variability, and six-minute walking test distance Results: Both exercised groups showed higher values in cardiovascular autonomic modulation, biochemical markers, and exercise tolerance after the exercise training program. The exercised kidney-transplanted patients group showed higher values in cardiovascular autonomic modulation, biochemical markers, and exercise tolerance when compared to the exercised hemodialysis patients group. Both groups showed improvements in sleep quality, anxiety, and depression. The group of kidney-transplanted patients show higher values in the cardiovascular autonomic modulation than subjects undergoing hemodialysis. However, the patients undergoing hemodialysis showed improvements in blood pressure, HDL, hemoglobin and phosphorus, changes not observed in the kidney-transplanted group. Conclusions: Exercise is beneficial for both hemodialysis and kidney-transplanted patients groups. However, exercise programs should be focused mainly in improving cardiovascular risk factors in the hemodialysis patients.